Unillanos promotes inclusion through sign language in classrooms (Contexto (Universidad de los Llanos), 2024)
In an effort to break down communication barriers between hearing students, teachers and administrators and deaf students, Universidad de los Llanos has implemented inclusion processes that are transforming the university community. One of the pillars of this initiative is the mentoring led by Michael Stiven Vásquez Barrera, a deaf student in the Bachelor of Physical Education and Sports program.Michael has taken the initiative to teach basic Colombian sign language to the Unillanista community. Through dedicated courses, he has taught essential vocabulary so that hearing people can gradually adapt to communicating with deaf people. “I was the only deaf person who committed myself to the learning of these hearing people, since we, as deaf people, have a different culture and language and require contact and communication. Even though we are different and have our own identity, we want them to be able to learn to communicate,” explained the student.
Keywords: inclusion; sign language; communication; community